(untitled) (Ameghiniana, 2014)
New materials of the octodontid rodent Neophanomus biplicatus Rovereto were recovered from sediments of the Cerro Azul Formation in La Pampa Province. They suggest a Late Huayquerian age for the fossiliferous beds. Analysis of the molar ontogeny in this species shows a greater morphological diversity than previously recognized. The holotype of "Eumusops" paroidens Rovereto (originally referred to the Echimyidae) is a young individual of this species. Neophanomys biplicatus is related to the extant species Octodontomys gliroides Gervais and d’Orbigny and to the Miocene lineage that includes Chasichimus Pascual. These primitive octodontids may have been members of a basal radiation from which the subfamily Ctenomyinae differentiated.